ED50 of ciprofol combined with different doses of remifentanil during upper gastrointestinal endoscopy in school-aged children: a prospective dose-finding study using an up-and-down sequential allocation method - Zhang, Xu; Zhang, Ning; Song, Haicheng; Ren, Yueyi (Frontiers in Pharmacology, 2024)
Objective This study aimed to determine the 50% effective dose (ED50) of ciprofol when combined with different doses of remifentanil for upper gastrointestinal endoscopy of school-age children and to evaluate its safety. Methods This study involved school-aged children who were scheduled to undergo upper gastrointestinal endoscopy under deep sedation. The children were randomly assigned to two groups: remifentanil 0.3 μg/kg (R0.3) and remifentanil 0.5 μg/kg (R0.5). Anesthesia was induced with remifentanil, followed by ciprofol. The dose of ciprofol for each patient was determined using the Dixon up-down sequential method. If the MOAA/S score was ≤1 and the child did not exhibit significant movement or coughing during the endoscopy process, sedation was considered successful. The first patient in each group received 0.5 mg/kg ciprofol. The dose of ciprofol was adjusted by 0.05 mg/kg based on the response of the previous patient. The primary outcome was the ED50 of the ciprofol-induction dose. The total ciprofol doses, onset times, awakening times, and adverse reactions were recorded. Results 1) The Dixon method was used to collect crossovers data from each group, and the ED50 values of the R0.3 and R0.5 groups were calculated to be 0.390 mg/kg (95% CI 0.356–0.424 mg/kg) and 0.332 mg/kg (95% CI 0.291–0.374 mg/kg), respectively. The ED50 of ciprofol in the R0.3 group was significantly higher than that in the R0.5 group (p < 0.05). 2) The onset time and recovery time of the R0.5 group were shorter than those of the R0.3 group (p < 0.05). When the two groups were compared, the total dose of ciprofol in the R0.5 group decreased (p < 0.05). 3) Compared with the R0.3 group, the incidence of respiratory depression during induction in the R0.5 group increased (p < 0.05). Conclusion This study explored the ED50 of ciprofol combined with different doses of remifentanil for successful sedation in upper gastrointestinal examinations in school-aged children. Compared to the use of remifentanil 0.3 μg/kg, the combination of ciprofol with remifentanil 0.5 μg/kg significantly reduced the ED50 required to prevent body movement or cough during endoscope insertion but increased the incidence of respiratory depression.